Ensaios para um quebra-cabeça a se desmontar: o romantismo, nosso contemporâneo, na poética de Omar Salomão - FHILIPE GERMANO RIGAMONTE (2023)
Based on the considerations of Candido (1988) and Löwy & Sayre (2015), romanticism, transcending its period of origin, comes to be exercised as an aesthetic that makes use of a worldview opposed to modernity. In this way, the continuity of romanticism conditions forms and themes to a revolt against the incarceration of subjectivity marked by false ideals of freedom, universality and progress, sustained by modernity. Especially as a consequence of the split in Enlightenment thought which leads to the incompatibility between the signifier and the signified, authors such as F. Schlegel (1994) and Benjamin (2011) consider the relative incompleteness of the fragment as a way out of the crisis in language brought about by the perverse modern dichotomy, thus, they build an aesthetics capable of manifesting the insufficiency of language. making it more and more "non-specific". Thus, it uses the essay as form (ADORNO, 2003) to read the poetics of Omar Salomão as an active object in a generation of poets, whose work with fragmented form is translated into the desire to oppose the illusions and contradictions of their reality. Therefore, Solomon displays a fragment-poetry which remains in an in-between place, contradicting and corroborating the modern project, whose incompleteness dismantles an ideal of universality, while trying to reconstruct another in its place. KEYWORDS: Romanticism; Fragment; Omar Salomon; Brazilian contemporary poetry.